Management of ankle valgus in a skeletally immature patient by tension band plate hemiepiphysiodesis: A case report (Indian Journal of Case Reports, 2021)
Temporary hemiepiphysiodesis is the procedure of choice to correct ankle valgus deformity in a skeletally immature patient. However, the literature is inconclusive regarding the ideal choice of implant and the timing of the surgery. In the current case report, a 9-year-old girl with multiple hereditary exostoses and unilateral ankle valgus deformity underwent tension band plate (TBP) hemiepiphysiodesis, and gained a modest correction at a rate of 0.61°/month. After 18 months of follow-up, there were no implant-related complications, and the functional outcome was also good. This case report shows a promising result of medial malleolar temporary hemiepiphysiodesis using a TBP for ankle valgus deformity in the pediatric population.